Core library of Puerto Cabezas - Lau Williams, Violeta (1980)
After the new change that lives through the country of Nicaragua in political, social, economic, cultural and educational topics. The new librarian must be a revolutionary in his field since it will correspond to him to assume extremely important charges in which it will have to demonstrate his skills. This project was elaborated after approximately three months of intensive studies in the branch of the Bibliotecología and whose acquired knowledge have to of be putting into practice in order that the Network of School Libraries to be implanting in Nicaragua, scope a total success.